Opportunities for Teaching the Topic “Fergana Economic Geography District” In the 8th Grade Geography Textbook Using Interactive Techniques - Isayev, A.; Arabbayev, A. (European Journal of Life Safety and Stability (2660-9630), 2022)
It is known that the process of teaching is a pedagogical and educational cognitive activity of students(pupils)of the teacher, aimed at achieving didactic goals. The concept of "Interactive “is expressed in English as” interact“, in Russian as” interactiv“, the lexical meaning of” inter “ – means interaction, Two – Way,” act" - Act, Act. In addition to the methods, the style is also one of the concepts close to each other in meaning. A person who has mastered the technique of doing something can do the same work more easily, quickly and smoothly than others. And a person who does not master the technique, he spends a lot of time and effort on this work. In this article we will talk about the possibilities of teaching the topic “Fergana economic geography district” in the 8th grade geography textbook using interactive techniques. American psychologist scientists R in the preparation of this article. Garnikau and F. The results of the study of makelro were used as well as several educational-methodical manuals of professors and teachers, conference materials and scientific journals.